Peningkatan Aktivitas dan Hasil Belajar Menggunakan Model Discovery Learning Berbantuan Media Pop-Up Book Pada Pembelajaran Tematik - Yurizki, Seli; Lusa, Herman; Yusnia (JURIDIKDAS, 2024)
This research aims to improve student activity and learning outcomes by using the Discovery Learning model assisted by  pop-up book media in class IIIA thematic learning at SDN 44 Bengkulu City. The subjects in this research were 21 teachers and students of class IIIA SDN 44 Bengkulu City. Test data is used using the formula for average value and percentage of learning completeness. Cycle I mathematics subjects with an average value of 45.72 and a percentage of 38.09% increased in cycle II with an average value of 76.66 and a percentage of 85.72%. So it can be concluded that classroom action research increased learning activities and outcomes using the Discovery Learning model assisted by  pop-up book media in class IIIA thematic learning at SDN 44 Bengkulu City.